Focusing of Electromagnetic Wave from Quartic Inhomogeneous Chiro-Slab - Ghaffar, A.; Sharif, M.; Naqvi, Q. A.; Alkanhal, M. A. S.; Khalid, F.; Shukurullah, S. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The focusing of electromagnetic waves from a quartic inhomogeneous chiro-slab is examined, using Maslov’s method. Analytic field expressions are derived for the transmission coefficients at the interfaces and numerical computations are made to determine the field behavior around the caustic point of the chiro-slab. The effects of chirality parameter, permittivity and permeability on the intensity of the field around caustic point of the chiro-slab are also discussed. The results obtained through this method are shown to be in good agreement with those obtained from Huygens Kirchhoff’s integral.